An introduction towards automated parameterization reduction of soft set - Bakshi T.; Sinharay A.; Som T. (My University, 2025)
In this paper, we introduce seven correlated algorithms for reduction of decision making parameters. This reduction framework is heuristic function based. The reduction of soft set decision parameters, those are collectively sufficient and individually necessary for keeping any special characteristic of a given information system. There has been very few works done on the algorithmic reduction techniques of decision parameter of soft set To the best of our knowledge, the computing complexities of available methods are of exponential order. We claim that our method is the first such kind of algorithms having polynomial time of computation. Illustrative example demonstrates the process elaborately. © 2016 IEEE.